DISSERTATION TITLE: TENSILE AND TRIBOLOGICAL PROPERTIES OF BENTONITE NANO CLAY FILLED HIGH DENSITY POLYETHYLENE POLYMER NANO COMPOSITE - AHMED, TAUSEEF (2020)
The tensile and wear properties of a material are equally dependent upon the stress transfer from soft polymeric phase to rigid particle phase. However, high density polyethylene (HDPE) becomes extremely brittle in an attempt to enhance the stress transfer with non-treated rigid filler particles for achieving enhanced mechanical and tribological properties. Therefore, this work focuses on achieving pseudo-ductility (high strength + ductility) and enhanced tribological properties, using a combination of rigid filler particles (CaCO3 + bentonite nanoclay), instead of a single non-treated rigid filler particle. The composite is fabricated by non-surface coated rigid filler particles in a twin-screw extruder. The characterization of the tensile and wear test is conducted by FESEM analysis to verify the assertion constructed in tensile and wear test.